Screening for exopolysaccharide production from basidiomycetes of chhattisgarh - Yogita, Rajput; Simanta, Shit; Aparna, Shukla; Shraddha, Gupta; Kamlesh, Shukla (Current Botany, 2011)
Polysaccharides extracted from mushrooms have wide applications. Seven species of mushroomsÂ i.e. Grifola frondosa, Polyporus species 1, Polyporus species 2, Pleurotus sajorcaju, Pleurotus florida, Schizophyllum commune and Jelly species were collected and each species was tested for their polysaccharide producing ability. Among all seven species, Pleurotus sajorcaju produces maximum exopolysaccharide & minimum was produced by Pleurotus florida 1. Polysaccharide production was checked by incubating all seven species in shaking and static conditions. Although 28Â°C at 150 rpm for 7 and 14 days is the best conditionÂ for exopolysaccharide production from mushroom species. Total biomass (dry weight and wet weight) was also recorded. Maximum biomass was found to be of Schizophyllum commune. Total free glucose produced was also determined and was found to be highest in Pleurotus florida. Natural polysaccharides can play a relevant role in biomedical and pharmaceutical applications, particularly in the field of drug delivery, for their intrinsic biocompatibility and potential low cost.